Existence, uniqueness solution for nonlinear mixed problem in two dimensional elasticity - Jaouad, Oudaani; Qualifiant, Enseignant au Lycee; a Khenifra, Ajdir (International Journal of Applied Mathematical Research, 2014)
The aim of this article is to minimises the stored energy function, of two dimensional elasticity with mixed boundary condition, in order, that the Euler's equilibrium equations of the Saint-Venant-Kirchhoff problem, has one and only one solution. Keywords: Elasticity, Saint-Venant, Stored Energy.